2013
DOI: 10.2478/s11686-013-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis on the body surface of pyrethroid-sensitive and resistant Varroa destructor

Abstract: The aim of this work was to determine the activity of proteases and protease inhibitors sampled from the body surface of taufluvalinate-sensitive and resistant V. destructor. Proteins were isolated from the tau-fluvalinate-sensitive and resistant mites, while mites untreated with tau-fluvalinate constituted the control. Subsequently, the following methodology was applied: protein concentration assay by the Lowry method -as modified by Schacterle and Pollack; assay of proteolytic activity in relation to various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…Pyrethroids are metabolized by hydrolysis of ester bonds, oxidation at the acid and alcohol moieties, and several conjugation reactions such as hydrophilic and lipophilic conjugates (Mikata, Osobe, & Kaneko, 2011;Strachecka, Borsuk, Olszewski, Paleolog, & Lipiński, 2013). Here, a number of proteins involved in hydrolysis (processing peptidase beta subunit putative, acetyl-CoA hydrolase putative, aminoimidazole-4-carboxamide ribonucleotidetransformylase/IMP were present in higher levels in pyrethroid resistant mites (Table 2) and these could be potential effectors of the more efficient breakdown of the chemical in resistant mites.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethroids are metabolized by hydrolysis of ester bonds, oxidation at the acid and alcohol moieties, and several conjugation reactions such as hydrophilic and lipophilic conjugates (Mikata, Osobe, & Kaneko, 2011;Strachecka, Borsuk, Olszewski, Paleolog, & Lipiński, 2013). Here, a number of proteins involved in hydrolysis (processing peptidase beta subunit putative, acetyl-CoA hydrolase putative, aminoimidazole-4-carboxamide ribonucleotidetransformylase/IMP were present in higher levels in pyrethroid resistant mites (Table 2) and these could be potential effectors of the more efficient breakdown of the chemical in resistant mites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insecticides induce physiological changes in mosquitoes such as a thickening of the epidermis, which subsequently lowers their permeability to insecticides (Wood et al 2010). Studies investigating the mechanisms of pyrethroid resistance have identified other resistance-related genes, such as UDP-glycosyltransferases , Bozzolan et al 2014) and serine proteases (Reid et al 2012, Strachecka et al 2013.…”
mentioning
confidence: 99%
“…Wiadomo, że metaloproteazy produkowane przez każdą z grup patogenów wpływają na indukcję humoralnej reakcji obronnej u owadów. Wydzielane są wówczas u owadów inhibitory skierowane przeciwko proteazom bakterii, grzybów i pasożytów (14,35). Z kolei poziom ekspresji mRNA metaloproteaz regulowany jest poziomem lipopolisacharydu (LPS) po inwazji bakteryjnej.…”
Section: Metaloproteazy I Ich Inhibitory U Owadówunclassified
“…Interakcja enzym MMP-inhibitor MMP jest uzależniona od warunków atmosferycznych (sezonowa zmiana metabolizmu) oraz od wydzielania feromonów pszczelich (7,39). Najprawdopodobniej u pszczół, podobnie jak u mrówek (8, 9) metaloproteazy tworzą wraz z innymi elementami systemu proteolitycznego ochronny biofilm na powierzchni ciała (15,35,36). U Manduca sexta po infekcji patogenami, głównie bakteriami, następuje wzmożona synteza metaloproteaz, które włączane są również w mechanizmy melanizacji (17).…”
Section: Metaloproteazy I Ich Inhibitory U Owadówunclassified